2018
DOI: 10.1152/ajprenal.00199.2018
|View full text |Cite
|
Sign up to set email alerts
|

Rodent models of AKI-CKD transition

Abstract: Acute kidney injury (AKI) is a contributing factor in the development and progression of chronic kidney disease (CKD). Despite rapid progresses, the mechanism underlying AKI-CKD transition remains largely unclear. Animal models recapitulating this process are crucial to the research of the pathophysiology of AKI-CKD transition and the development of effective therapeutics. In this review, we present the commonly used rodent models of AKI-CKD transition, including bilateral ischemia-reperfusion injury (IRI), un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 72 publications
(107 reference statements)
2
131
0
2
Order By: Relevance
“…In renal IRI models, ischemic duration and kidney temperature are two key determinants for the severity of AKI. The time length of renal pedicle clamping in mice varied from 14 to 90 min, with plasma creatinine values from 1.4 to 2.8 mg/dl, in different laboratories (13,22,28,39,53). We think that the huge variation in ischemic time and renal injury is mainly because of the kidney temperature during ischemia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In renal IRI models, ischemic duration and kidney temperature are two key determinants for the severity of AKI. The time length of renal pedicle clamping in mice varied from 14 to 90 min, with plasma creatinine values from 1.4 to 2.8 mg/dl, in different laboratories (13,22,28,39,53). We think that the huge variation in ischemic time and renal injury is mainly because of the kidney temperature during ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…Several experimental animal models for AKI to CKD transition have been generated, which are widely used and have advanced our understanding of the pathophysiological mechanisms for the transition from AKI to CKD. However, none of them exhibit the typical changes in GFR and PCr, the hallmarks of AKI to CKD transition (3,13,56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that FA has nephrotoxic activity at various levels of the nephron because it induces a pro-oxidant state by increasing lipid binding and reducing protective anti-oxidant enzymes (Gupta et al 2012). It has been suggested recently that the residual structural damage that is produced by FA could lead to CKD pathology (Fu et al 2018). Creatinine and BUN levels have been used traditionally in clinical practice as markers of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…This has been suggested to lead to an alteration in cellular architecture and generate oxidative stress and fibrosis that could progress to CKD (Stallons et al 2014). Fu et al hypothesized that the repeated injury by multiple administrations of FA could be sufficient to cause the transition from AKI to CKD (Fu et al 2018). To establish whether the pharmacological AKI induced by repetitive FA dosing progresses to CKD, the effect of FA on distinctive parameters of renal function must be explored.…”
Section: Introductionmentioning
confidence: 99%
“…For ischemic acute kidney injury, it was induced by the duration of bilateral clamping for 28 min and followed by reperfusion 43 . For cisplatin injury, mice were intraperitoneally injected with 10 mg/kg cisplatin at weeks 0, 1, and 3 44 . For aristolochic acid injury, mice were intraperitoneally injected with 250 mg/kg aristolochic acid 45 .…”
Section: Methodsmentioning
confidence: 99%